Effect of Spheroidizing and Normalizing Treatments on the Electromagnetic Behavior and Microstructural Transformations of Ferritic-Pearlitic Steel Wire for Flexible Marine Pipelines - Samille Kricia B. de Lima; Juan Manuel Pardal; Leosdan Figueredo Noris; Pedro Henrique P. Lima; João Victor B. Xavier; Hamilton Ferreira G. de Abreu (Materials Research, 2025)
The tensile armor of flexible marine pipelines, responsible for the flow of oil and gas, is composed of the helical arrangement of steel wires subjected to complex stress modes that can cause unpredictable failures. Electromagnetic non-destructive testing (NDT) techniques are suitable for monitoring microstructural, morphological, and mechanical properties changes in deformed or heat-treated steels. In this study, a steel used in the manufacture of flexible Risers subjected to different heat treatments, with time and temperature variation, was investigated by SEM, XRD, and DSC, and related to the behavior of MBN, Magnetic Hysteresis, and Electrical Resistivity signals. The results indicate that the recovery process occurs in the spheroidizing at 600 and 700 °C; however, the behavior of the MBN envelope and the DSC curves suggest that the recrystallization only occurs in the treatments at 700 and 800 °C. The MBN peak has greater amplitude and lower energy to reach saturation due to the increased mobility of domain walls in spheroidized microstructure. In normalizing, the MBN peak was lower and the electrical resistivity higher, as the pearlitic microstructure and the multiplication of grain boundaries in recrystallization cause greater impediment to the movement of domain walls and the flow of free electrons.